2021
DOI: 10.3390/jof7040280
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia among Iranian Patients with Severe COVID-19 Admitted to ICUs

Abstract: As a novel risk factor, COVID-19 has led to an increase in the incidence of candidemia and an elevated mortality rate. Despite being of clinical importance, there is a lack of data regarding COVID-19-associated candidemia (CAC) among Iranian patients. Therefore, in this retrospective study, we assessed CAC epidemiology in the intensive care units (ICUs) of two COVID-19 centers in Mashhad, Iran, from early November 2020 to late January 2021. Yeast isolates from patients’ blood were identified by 21-plex polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 34 publications
(73 reference statements)
1
86
2
Order By: Relevance
“…The 30-day mortality in this population was 89.5%, which is higher than the overall reported mortality of 68.5% (217/317) from ventilated patients at HUMC in the comparable time period [ 67 ]. The elevated mortality rate in COVID-19 patients with fungal superinfections, irrespective of the drug resistance profile of the infecting organism, is in agreement with other reports on COVID-19-associated candidemia [ 11 , 12 , 68 ].…”
Section: Discussionsupporting
confidence: 91%
“…The 30-day mortality in this population was 89.5%, which is higher than the overall reported mortality of 68.5% (217/317) from ventilated patients at HUMC in the comparable time period [ 67 ]. The elevated mortality rate in COVID-19 patients with fungal superinfections, irrespective of the drug resistance profile of the infecting organism, is in agreement with other reports on COVID-19-associated candidemia [ 11 , 12 , 68 ].…”
Section: Discussionsupporting
confidence: 91%
“…Prospective and retrospective data of COVID-19 patients admitted to intensive care units (ICU), especially for a prolonged duration, show that these patients are susceptible to invasive microbial co-infections during hospitalization and that these may lead to more severe outcomes [ 3 , 7 , 16 , 31 ]. A prospective cohort study of 135 adults, performed across multiple centers in Wales, showed a significantly higher (up to 25%) mortality rate in COVID-19 patients with fungal infections compared to patients without fungal infections [ 7 ].…”
Section: Fungal Co-infections In Covid-19 Disease: Disease Severity the Emergence Of Multidrug Resistance And Mucormycosismentioning
confidence: 99%
“…Reports from Italy indicate that up to 57.1% and 50% mortality was reported in COVID-19 patients with candidemia [ 57 ] and Candida auris candidemia [ 27 ], respectively. Elsewhere, the mortality rate of COVID-19 patients with candidemia exceeded those of counterparts without candidemia in Iran (100% vs. 22.7%) [ 31 ]. Altogether, these observations highlight and re-emphasize the propensity of fungal co-infections to exacerbate disease severity and, consequently, increase the mortality of critically ill patients admitted to the ICUs.…”
Section: Fungal Co-infections In Covid-19 Disease: Disease Severity the Emergence Of Multidrug Resistance And Mucormycosismentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, it is important to set a protocol to rapidly identify it in hospitalized patients; thus, health-care facilities can take special precautions and implementing effective infection control measures to stop its spread especially because some commonly used health-care disinfectants are not sufficiently effective against C. auris leads to its persistence in health-care environments for several weeks [8].…”
Section: Introductionmentioning
confidence: 99%